2004
DOI: 10.1038/oby.2004.17
|View full text |Cite
|
Sign up to set email alerts
|

β3 Adrenergic Receptor Polymorphism and Obesity‐Related Phenotypes in Hypertensive Patients

Abstract: Adrenergic receptor polymorphism and obesityrelated phenotypes in hypertensive patients. Obes Res. 2004;12:125-130. Objectives: Obesity is a complex trait that is affected by both environmental and genetic risk factors. The ␤ 3 adrenergic receptor (ADRB3) is expressed in adipose tissue and plays a role in energy metabolism. A missense mutation on codon 64 of this gene (W64R) is associated with receptor malfunction. Previous studies examining the relation between this polymorphism and obesity produced inconsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Hao et al (23) suggested no significant association of Trp64Arg polymorphism of the ␤3-adrenergic receptor gene with serum levels of triglyceride, cholesterol, or glucose in Chinese hypertensive women.…”
Section: Discussionmentioning
confidence: 99%
“…Hao et al (23) suggested no significant association of Trp64Arg polymorphism of the ␤3-adrenergic receptor gene with serum levels of triglyceride, cholesterol, or glucose in Chinese hypertensive women.…”
Section: Discussionmentioning
confidence: 99%
“…This SNP, T727C, encodes an amino acid substitution (Trp64Arg) in the first transmembrane-spanning region of ADRB3, near its N-terminus. In a series of 695 adult Chinese subjects, this ADRB3 SNP was associated with weight and BMI in men but not in women [52]. A similar effect was observed in 295 adult Japanese men, but only when the data were adjusted for energy intake [51].…”
mentioning
confidence: 56%
“…In a study of 643 American women (representing both European and African heritage), no association was observed between this ADRB3 SNP and any obesity phenotypes (i.e., BMI, waist circumference and waist:hip ratio [50]). The reason for gender discrepancy remains unclear and requires further characterization, since emerging data indicate that gender may impact phenotype in the context of glaucoma treatment [52].…”
Section: Adrb Genes As Pharmacodynamic Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations of SNPs at codons 16 and 27 of the ADRB2 gene with obesity have been reported (Ukkola et al 2000), yet the significance of ADRB2-1053G/C in our study was novel. The significance of a common ADRB3 variant replacing tryptophan with arginine (Trp64Arg) on BMI has been shown in both adult (Hao et al 2004) and children (Endo et al 2000;Arashiro et al 2003) populations. ADRB3-Trp64Arg also influenced percentage of body fat (P < 0.01) and plasma leptin level (P < 0.05).…”
Section: Resultsmentioning
confidence: 99%